All stakeholders are equal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
One Step Beyond. Multi-Stakeholder Processes for Governance and Sustainability By Minu Hemmati Earthscan/ Stakeholder Forum for Our Common Future, London, 2002. 328 pp. ISBN GBP 17.95 Euro 28.75